Pendekatan Psikoanalisis dan Teologi Kristen Terhadap Kesehatan Mental Remaja Kristen Akibat Pembelajaran Jarak Jauh - David Ferdinan Tampubolon; Puja Sri Raso Devi Tampubolon; Samuel Siringoringo (JURNAL LUXNOS, 2021)
Abstract: The purpose of distance learning during the COVID-19 virus pandemic is to prevent the spread and transmission of the virus in the education unit environment. However, in the implementation of distance learning, students experience several obstacles. These obstacles lead to mental health problems for Christian adolescents, namely: anxiety, fear, stress, anger, disappointment, and sadness. This study aims to address the mental health of Christian adolescents as a result of distance learning through the approach of Psychoanalysis and Christian Theology. The subjects of this study were Christian adolescents and the object of this research was the mental health of Christian adolescents themselves. This study uses qualitative research methods with case studies and narrative Cresswell models. The data analysis technique used by the researcher is the Miles and Huberman model through data reduction activities, data presentation, conclusion drawing and data verification. The result of this study is that the psychoanalytic approach helps Christian adolescents in dealing with mental health problems by restoring the ego function that has been traumatized from the environment, family, and past experiences. Meanwhile, the Christian theology approach prioritizes spirituality, namely the relationship between humans and God in all aspects of human life.  Abstrak: Tujuan pembelajaran jarak jauh di masa pandemi virus COVID-19 yaitu mencegah penyebaran dan penularan virus tersebut di lingkungan satuan pendidikan. Namun dalam pelaksanaan pembelajaran jarak jauh, peserta didik mengalami beberapa kendala. Kendala tersebut menengakibatkan masalah bagi kesehatan mental remaja Kristen, yaitu: kecemasan, ketakutan, stres, marah, kecewa, dan sedih. Penelitian ini bertujuan untuk menyikapi kesehatan mental remaja Kristen akibat pembelajaran jarak jauh melalui pendekatan Psikoanalisis dan Teologi Kristen. Subjek penelitian ini adalah remaja Kristen dan objek penelitiain adalah kesehatan mental dari remaja Kristen itu sendiri. Penelitian ini menggunakan metode penelitian kualitatif dengan studi kasus dan naratif model Cresswell. Teknik analsisis data yang digunakan oleh peneliti adalah model Miles dan Huberman melalui kegiatan reduksi data, penyajian data, penarikan kesimpulan dan verifikasi data. Hasil dari penelitian ini yaitu pendekatan psikoanalisis membantu remaja Kristen dalam menangani masalah kesehatan mental dengan mengembalikan fungsi ego yang mengalami trauma dari lingkungan, keluarga, dan pengalaman masa lalu. Sedangkan, pendekatan Teologi Kristen mengutamakan spiritual yaitu adanya hubungan antara manusia dengan Tuhan dalam segala aspek kehidupan manusia.